Compositional and Functional Microbiome Variation Between Tubes of an Intertidal Polychaete and Surrounding Marine Sediment - Fuirst, Matthew; Ward, Christopher S.; Schwaner, Caroline; Diana, Zoie; Schultz, Thomas F.; Rittschof, Daniel (Frontiers in Marine Science, 2021)
The decorator worm Diopatra cuprea, a tube-forming marine polychaete common to intertidal and shallow subtidal waters, modifies habitats it occupies through microreef construction and algal gardening. While several studies have demonstrated that decorator worm tubes are hotspots of biogeochemical activity (i.e., nitrogen and sulfur cycling), it is still largely unclear whether the tube microbiome differs compositionally from the surrounding sediment and what distinct functional processes tube microbiomes may have. To address these unknowns, this study analyzed the bacterial communities of D. cuprea tubes and surrounding sediments using high-throughput 16S rRNA gene amplicon sequencing. Tubes and sediments were sampled at three sites along an anthropogenic stress gradient within the Newport River Estuary to also assess geographic variation of tube microbiomes and the possible influence of human disturbance. We found a clear distinction in the microbial community composition and diversity between tubes and surrounding sediment. Tube microbiomes were significantly enriched for the phyla Bacteriodetes, Actinobacteria, Verrucomicrobia, Deferribacteres, Latescibacteria, and Lentisphaerae. Chloroplast sequences of macroalgae and grass species were consistently abundant in tubes and nearly absent in surrounding sediment. Functional annotation of prokaryotic taxa (FAPROTAX)-based functional predictions suggested that tube microbiomes have higher potentials for aerobic chemoheterotrophy, sulfur compound respiration, nitrate reduction, methylotrophy, and hydrocarbon degradation than surrounding sediments. Tube microbiomes vary across sites, though dissimilarity is comparatively low compared to tube-to-sediment differences. Contrary to our hypothesis, the tubes at the most highly impacted site had the highest microbial diversity [i.e., amplicon sequence variant (ASV) richness and Shannon’s diversity], yet tubes from the medium impacted site actually had the lowest microbial diversity. Our findings show that D. cuprea tubes support a microbiome that is significantly distinct in composition and function from the surrounding sediment. Diopatra cuprea tubes appear to create unique microhabitats that facilitate numerous microbially-mediated biogeochemical processes in the marine benthic environment.